Direct‐Drive Acoustic Amplification Using a Tympanostomy Tube. (23rd August 2013) - Yau, Yuk Y.A.; Mahboubi, Hossein; Malley, Melinda J.D.; Conderman, Christian P.; Paulick, Peyton; Bachman, Mark; Djalilian, Hamid R.
Abstract : Objectives: Determine whether a tympanostomy tube with a ferromagnetic cap can be actuated to deliver sound to the cochlea. Methods: A ferromagnetic mixture of nickel powder and epoxy was glued to the outer flange of an Armstrong V Grommet tympanostomy tube. The tube was then placed into the pars tensa portion of a cadaveric temporal bone. The Direct‐Drive Hearing Device (DHD), a completely‐in‐the‐canal hearing aid prototype developed in our lab, was coupled to the nickel‐epoxy flange and fixed inside the ear canal. The displacements of the posterior crus of the stapes were then measured using a Laser Doppler Vibrometer. The range of displacements induced by the device was compared to those of natural sound. Results: A 200 mV input to the device produced a range of displacements equivalent to those of sound at 70 dB sound pressure level (SPL; mean 0.44 nm; range 0.01‐2.80). A 400 mV input produced a range of displacements equivalent to those of sound at 80 dB SPL (mean 1.34 nm; range 0.02‐8.87). Conclusions: DHD, a small completely‐in‐the‐canal hearing aid prototype, is capable of actuating the TM through a ferromagnetic tympanostomy tube and producing range of displacements equivalent to moderate to severe levels of hearing loss.